2016
DOI: 10.5826/dpc.0603a06
|View full text |Cite
|
Sign up to set email alerts
|

Diet and eczema: a review of dietary supplements for the treatment of atopic dermatitis

Abstract: In the context of increasing popularity of “natural” alternatives to conventional medicine, several dietary supplements have gained the attention of researchers and consumers alike in the treatment of atopic dermatitis (AD). Readily available without a prescription and frequently perceived to have fewer side effects than traditional medications, these “natural” remedies may be featured in discussions with patients, and clinicians should therefore be familiar with their efficacy and safety.Based on trials to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
0
22
0
2
Order By: Relevance
“…Despite some conflicting results [48, 49], case-controlled studies of AD sufferers have shown higher blood levels of linoleic acid (precursor of n-6 PUFA) and lower levels of n-3 PUFA [50, 51]. However, from studies in literature concerning the effects of diet on AD [5256] emerges that a strict diet management is not effective in general in the treatment of AD [57]. Further studies are therefore needed in this regard [9].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Despite some conflicting results [48, 49], case-controlled studies of AD sufferers have shown higher blood levels of linoleic acid (precursor of n-6 PUFA) and lower levels of n-3 PUFA [50, 51]. However, from studies in literature concerning the effects of diet on AD [5256] emerges that a strict diet management is not effective in general in the treatment of AD [57]. Further studies are therefore needed in this regard [9].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…It was found that oral treatment with evening primrose oil, which contains γ-linolenic acid, may lead to a reduction in the symptoms of atopic dermatitis [ 22 ]. However, subsequent studies have not confirmed that oral supplementation with evening primrose oil improves the skin condition in patients with atopic dermatitis [ 23 ].…”
Section: Biological Activity Of Evening Primrose Oil ( Omentioning
confidence: 99%
“…Epidemiological studies have shown an increased AD prevalence in populations living in higher geographic latitudes, with lower sun exposure and consequently less vitamin D production [115,116]. Also, in large population-based studies, it was observed that there is an increased likelihood of developing AD in individuals with either deficient or insufficient vitamin D levels [117,118].…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%